Assembly of Genetically Engineered Ionizable Protein Nanocage-based Nanozymes for Intracellular Superoxide Scavenging - Qiqi Liu; Zhanxia Gao; Xiangyun Zhang; Qiannan Duan; Yue Zhang; Adam C. Midgley; Li Jiao; Ruming Liu; Mingsheng Zhu; Deling Kong; Jie Zhuang; Xinglu Huang (Nature Communications)
Abstract Nanozymes play a pivotal role in mitigating excessive oxidative stress, however, determining their specific enzyme-mimicking activities for intracellular free radical scavenging is challenging due to endo-lysosomal entrapment. In this study, we employ a genetic engineering strategy to generate ionizable ferritin nanocages (iFTn), enabling their escape from endo-lysosomes and entry into the cytoplasm. Specifically, ionizable repeated Histidine-Histidine-Glutamic acid (9H2E) sequences are genetically incorporated into the outer surface of human heavy chain FTn, followed by the assembly of various chain-like nanostructures via a two-armed polyethylene glycol (PEG). Utilizing endosome-escaping ability, we design iFTn-based tetrameric cascade nanozymes with high superoxide dismutase- and catalase-mimicking activities. The in vivo protective effects of these ionizable cascade nanozymes against cardiac oxidative injury are demonstrated in female mouse models of cardiac ischemia-reperfusion (IR). RNA-sequencing analysis highlight the crucial role of these nanozymes in modulating superoxide anions-, hydrogen peroxide- and mitochondrial functions-relevant genes in IR injured cardiac tissue. These genetically engineered ionizable protein nanocarriers provide opportunities for developing ionizable drug delivery systems.